Hillside houses and log cabins, including that of William and Mabel Meed, Dawson, Yukon Territory, 1902. - Meed, William E.
PH Coll 246.244 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number